2019
DOI: 10.3892/etm.2019.8052
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of competing endogenous RNA networks associated with cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is the second most common type of primary malignancy of the liver. Certain long non-coding RNAs (lncRNAs) have been demonstrated to have key roles in tumor pathogenesis by binding to microRNAs (miRNAs). However, the competing endogenous RNA (ceRNA) network of CCA remains to be fully determined. In the present study, the RNA expression profiles for CCA were downloaded from The Cancer Genome Atlas and further analyzed. A total of 318 differentially expressed (DE) lncRNAs, 87 DE miRNAs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…[45] PPAR-α upregulation Tumor occurrence and progression in CCA patients with. [46,47] IDH1 and IDH2 mutations Increase of glucose uptake and glucose metabolism as well as upregulation of some metabolites in TCA cycle. Upregulation of PFKP.…”
Section: Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] PPAR-α upregulation Tumor occurrence and progression in CCA patients with. [46,47] IDH1 and IDH2 mutations Increase of glucose uptake and glucose metabolism as well as upregulation of some metabolites in TCA cycle. Upregulation of PFKP.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…The analysis performed has revealed that the genes identified were strongly linked to metabolism. Pathway analysis has found that carbon metabolism, bile secretion, fat digestion, and PPAR signaling pathway were processes significantly enriched and played a pivotal role in CCA patients [46] (Table 1).…”
Section: Nuclear Receptors: Farnesoid X Receptor (Fxr) and Peroxisomementioning
confidence: 99%
“…OSER1-AS1 was found to be mostly located in the cytoplasm of NSCLC cells. Increasing evidence suggests that cytoplasmic lncRNAs can act as competitive endogenous RNAs (ceRNAs) and thereby competitively bind to the target sites of miRNAs, leading to the release of target mRNAs (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the ceRNA hypothesis of crosstalk between ncRNAs and mRNAs has received much attention and is considered a new measure of gene regulation at the posttranscriptional level, which provides new insight into revealing mechanisms of tumorigenesis and identifying potential diagnostic and prognostic biomarkers. A growing number of published studies have demonstrated that many predictive signatures are detected in various tumors based on ceRNA network analysis [29][30][31][32][33]. MiRNAs, included in ncRNAs, are identified to be evolutionarily conserved, with an average length of 22-nt, and may bind to the 3'untranslated region (3'UTR) of the targeted mRNAs according to the principle of complementary base pairing.…”
Section: Discussionmentioning
confidence: 99%